Pengaruh Pengawasan dan Motivasi terhadap Kinerja Pegawai Aparatur Sipil Negara Dimediasi oleh Disiplin Kerja pada Dinas Perpustakaan dan Kearsipan Kota Medan - Aulia Chairani; Hazmanan Khair (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
Supervision is a function in functional management that must be carried out by each leader of all units or work units on the implementation of work or employees who carry out in accordance with their respective main tasks. Motivation is a variety of efforts made by humans, of course, to fulfill their wants and needs. Work discipline is an attitude that is obedient to the rules and norms that apply in a company in order to increase the constancy of employees in achieving company or organizational goals. While performance is a science that combines art in it to apply a management concept that has a representative and aspirational level of flexibility in order to realize the vision and mission of the agency by using people in the organization. The population in this study were all employees of the state civil apparatus at the Medan City Library and Archives Service, amounting to 54 people, while the sample was the total population of 54 people. Data collection techniques using a list of questions such as questionnaires and data analysis techniques using Partial Least Square (SmartPls) to test the seven hypotheses proposed in this study. The results of the research show that: (1) the effect of supervision on performance is positive and significant; (2) the effect of motivation on performance is negative and not significant; (3) the effect of supervision on work discipline is positive and significant; (4) the effect of motivation on work discipline is negative and insignificant; (5) the effect of work discipline on performance is positive and not significant; (6) work discipline mediates the effect of supervision on performance is positive and not significant; (7) work discipline mediates the effect of motivation on performance is negative and not significant.